Effects of Purple Sweet Potatoes on Oxidative Stress Biomarkers in Rats Subjected to Exhaustive Exercise - Sholikhah, Anindya Maratus`; Wirjatmadi, Bambang; Adriani, Merryana (Health Notions, 2018)
Oxidative stress is a condition caused by the imbalance between the production of free radicals or ROS and the antioxidants; the level of free radicals is higher than the antioxidants. Exhaustive exercise is one of the causes of this oxidative stress. However, it can be reduced by antioxidants found in purple sweet potatoes (PSP) (Ipomoea batatas L). This study aims to evaluate the effect of two weeks supplementation of PSP extract on rats inducedoxidative stress. Twenty rats were distibuted into four groups consisted five rats each. Rats in the treatments groups were administered PSP extract for two weeks then were forced to swim until exhausted. Bloods from all samples were drawn to see the changes in the levels of malondialdehyde ans superoxide dismutase after two weeks of treatment. The data was then analyzed using descriptive and inferential statistic. The results showed that mean level of MDA and SOD differ significantly (p<0.05) between groups after the administration of PSP extract as well as after exhaustive exercise. The extracts and exhaustive exercise concurrently showed a significant effect on oxidative stress biomarkers (p<0.05). It concluded that PSP extract can protect cells against free radical produced by exhaustive exercise.